solve 3x2 18x 15 = 0 by completing the square.

a. 3(x 3)2 = 6; x = −3 square root 2, x = −3 − square root 2
b. 3(x 9)2 = 12; x = −11, x = −7
c. 3(x 3)2 = 12; x = −5, x = −1
d. 3(x 9)2 = 228; x = −9 square root 76, x = −9 − square root 76

Respuesta :

3(x^2 + 6x + 5) = 0
3(x^2 + 6x + 9 + 5 - 9) = 0
3(x + 3)^2 + 3(-4) = 0
3(x + 3)^2 - 12 = 0
3(x + 3)^2 = 12
(x + 3)^2 = 4
x + 3 = sqrt(4)
x = -3 + or - 2
x = -3 + 2 or -3 - 2
x = -1 or -5
The correct answer option is option c.

Answer:

c

Step-by-step explanation: